Addressing Early Adversity Through Mental Health Consultation in Early Childhood Settings. Issue 1 (February 2016) - Perry, Deborah F.; Conners‐Burrow, Nicola
Abstract: The science of early childhood adversity has advanced in recent years, documenting long‐term consequences of exposure to traumatic events and toxic stress for health and development. Sequelae of toxic stress exposure can be mitigated by the buffering effect of a caregiver who can help young children manage their reactivity to these early stressors. Interventions are needed to build the capacity for caregivers (including the early childhood workforce) to build resilience in young children exposed to early adversity. This article shares best practices from the field of early childhood mental health consultation (ECMHC) as a strategy to help reduce the impact of stressors on young children. ECMHC embedded with child care, focused on children in foster care, and lessons learned from early work on ECMHC in home visiting are highlighted as examples of interventions to build the buffering capacities of important adults in children's lives. Policy recommendations are offered for integrating mental health services into early childhood settings to build resilience in high‐risk children and families.